High-fiber basil seed flour reduces insulin resistance and hepatic steatosis in high-fat diet mice - Camila Farías; Camila Cisternas; Angie Caicedo; Lorena Mercado; Rodrigo Valenzuela; Héctor Calderón; Alejandra Espinosa; L. A. Videla; Loreto A. Muñoz (npj Science of Food)
Abstract The incidence of insulin resistance (IR) and hepatic steatosis is increasing, with dietary fiber playing a protective role against these disorders. Ocimum basilicum L., widely used in food, pharmaceutical, and cosmetic industries, but their health-promoting properties remain underexplored. This study evaluated the effects of a fiber-rich fraction of partially defatted basil seeds (BSF) on IR, hepatic steatosis, and polyunsaturated fatty acid and short-chain fatty acid (SCFA) profiles in high-fat diet (HFD)-fed C57BL/6 J male mice. Mice were assigned to four groups and fed either a control diet or HFD, supplemented with BSF or oat flour for 4 weeks. HFD induced IR, hepatic steatosis, proinflammatory state, and a significant decreased in SCFA production. In contrast, supplementation with BSF attenuated IR, steatosis, liver damage, oxidative stress, and inflammation, while increasing n-3 polyunsaturated fatty acids in liver, adipocytes, and erythrocytes, and enhancing SCFA production, suggesting potential therapeutic benefits in managing these conditions.